Evolutionary basis of communication facilitating human-pet interaction - Vsevolodovna, Nikolskaya Anastasia (Opción, 2019)
The paper describes processes occurring in heterospecific systems and the products generated by such systems, and the differences between the animal communication system and the human language via the method of observation for pet behavior and keeper behavior during the communication process. As a result, the signals that an animal sets to its keeper are always in the context of the situation and perceived by the keeper only in this context. In conclusion, there are general basic representations about the world in human and animals that facilitate heterospecific communication.